GCG Role and Audit Quality in Reducing Earnings Management Action in Indonesian Manufacturing Firms - Sigit Handoyo; Windri Bulan Agustianingrum (University of Merdeka Malang, 2017)
All elements in the financial statements were the responsibility of the management, however, investors more pay attention to profit information so that this will trigger the management to do earnings management. This study was intended to analyze the effect of managerial ownership, institutional ownership, independent board, audit committee, and the quality of audit toward earnings management. This study is using data 35 manufacturing companies listed on Indonesia Stock Exchange 2013-2015, determination of samples in this study using a purposive sampling method. The data of the managerial ownership, institutional ownership, independent board, audit committee and quality of audit were gathered from the company’s annual report. Hypothesis testing using multiple regression analysis. The outcome of the hypothesis testing shows that the managerial ownership, institutional ownership, audit committee and quality of audit will give a significant negative effect on earnings management while the independent board has no influence on earnings management.DOI: https://doi.org/10.26905/jkdp.v21i3.673